Synthesis and structural and spectral studies of a neodymium complex on the basis of N-[bis(pyrrolidint-1-yl)phosphoryl]-2,2,2-trichloroacetamide - Znovjyak, K. O.; Ovchynniko, V. A.; Sliva, T. Yu.; Moroz, O. V.; Shishkina, S. V.; Amirkhanov, V. M. (Reports of the National Academy of Sciences of Ukraine, 2015)
A new coordination compound with formula Nd(HL)3(NO3)3 (1), where HL = Cl3CC(O)NHP(O)(N(CH2)4)2, N-[bis(pyrrolidine-1-yl)phosphoryl]-2,2,2-trichloroacetamide, has been synthesized and characterized by means of IR and UV–VIS spectroscopy. Crystal structure of 1 has been determined by single-crystal X-ray diffraction. The coordination environment of the NdIII ion is a distorted tricapped trigonal prism. Three ligand molecules HL coordinate to the neodymium ion in a monodentate manner via oxygen atoms of the phosphoryl groups, while the nitrate groups coordinate in a bidentate manner. In the crystal structure, NO3−-groups are additionally involved in the intramolecular N−H· · ·ONO2 hydrogen bonding with the N−H groups of HL. On the basis of UV–VIS spectroscopic investigations, a conclusion is made about similar geometries of the coordination polyhedron in the crystalline state and in a benzene solution.